DEVELOPMENT OF A PROJECT-BASED LEARNING MODULE FOR INDONESIAN CAKE AND PASTRY PRODUCTS TO IMPROVE CREATIVITY AND CRITICAL THINKING SKILLS OF WIRA HARAPAN VOCATIONAL SCHOOL STUDENTS: Pengembangan Modul Pembelajaran Produk Cake dan Kue Indonesia Berbasis Proyek untuk Meningkatkan Kreativitas dan Kemampuan Berpikir Kritis Siswa SMK Wira Harapan - I Putu Pranatha Sentosa; Ni Made Erpia Ordani Astuti; Vinsensa Yuniarti Harmin; I Kadek Edo Purnawan; I Gusti Ayu Ika Monika Prastyandhari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The purpose of this research is to produce a project-based learning module of Indonesian Cake and Cake Products (PCKI) in accordance with the Vocational High School (SMK) curriculum that is valid, practical and effective to improve students' critical thinking skills in learning Indonesian cake and cake products (PCKI). This research uses Development (R&D), to produce new products or improve existing products using the ADDIE Development model. The research subjects were one content expert and a linguist for the validity test, one teacher and 6 students for the practicality test and the study group for the effectiveness test. The instruments used in this study are content and language validity tests, practicality test instruments, and effectiveness test instruments in the form of tests to increase students' creativity and critical thinking. The data collection techniques used are through observation, interviews, questionnaires, tests and documentation. Overall, the Aiken index showed a score of 0.897 in the "Valid" category, thus the instruments used to assess the validity of content based on content eligibility, presentation eligibility, language eligibility, and media eligibility, can be used to accurately measure. Based on the results of the analysis of the practicality test data above, it can be seen that the average score of practicality by teachers and students is 4.7 and 4.88 respectively with very good qualifications. This means that the Project-based Learning (PjBL) module produced in this study is practical to use. Based on the test using the Gregory formula, the results of the validity of the content above showed excellent results with a VI value of more than 90%, thus the entire instrument (questionnaire) for measuring creativity and critical thinking ability can be used without revision. The results of the normality test above showed a significance value of > 0.05 from each variable measured, namely in the creativity pretest, creativity posttest, critical thinking ability pretest, and critical thinking ability posttest. With these results, it can be concluded that all the measured variables have been distributed normally. Based on the results of the t-test carried out above, it can be said that the significance value for the creativity pretest and creativity posttest shows a significance value of < 0.05, thus it can be stated that with the teaching module Developed it is effective in increasing creativity. Furthermore, the significance value for the creativity pretest and posttest of critical thinking ability shows a significance value of < 0.05, thus it can be stated that the Developed teaching module is effective in improving critical thinking skills.